2021
DOI: 10.3390/jcm10071493
|View full text |Cite
|
Sign up to set email alerts
|

Balneotherapy for Fibromyalgia Syndrome: A Systematic Review and Meta-Analysis

Abstract: (1) Background: The efficiency of balneotherapy (BT) for fibromyalgia syndrome (FMS) remains elusive. (2) Methods: Cochrane Library, EMBASE, MEDLINE, PubMed, Clinicaltrials.gov, and PsycINFO were searched from inception to 31 May 2020. Randomized controlled trials (RCTs) with at least one indicator were included, i.e., pain, Fibromyalgia Impact Questionnaire (FIQ), Tender Points Count (TPC), and Beck’s Depression Index (BDI). The outcome was reported as a standardized mean difference (SMD), 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This finding was analogous to that of the previous study, 96 which reported a significant reduction in disease impact in older fibromyalgia patients after repetitive transcranial magnetic stimulation intervention. Likewise, Cao et al 97 found that balneotherapy significantly improved functional outcomes when compared with the controls. Evidence from preclinical studies suggests that transcranial magnetic stimulation, can alter synaptic plasticity, modify neural circuits and brain networks, and activate neurotransmitters.…”
Section: Discussionmentioning
confidence: 94%
“…This finding was analogous to that of the previous study, 96 which reported a significant reduction in disease impact in older fibromyalgia patients after repetitive transcranial magnetic stimulation intervention. Likewise, Cao et al 97 found that balneotherapy significantly improved functional outcomes when compared with the controls. Evidence from preclinical studies suggests that transcranial magnetic stimulation, can alter synaptic plasticity, modify neural circuits and brain networks, and activate neurotransmitters.…”
Section: Discussionmentioning
confidence: 94%
“…FMS is a chronic disease characterized by widespread muscle pain that reduces functional capability and QoL. In addition to other therapies, such as pharmacotherapy [72], balneotherapy [73] or physical exercise [74,75], VRBT has emerged as a new therapy that can reduce the impact of FMS symptoms. The present study proposed to compile the scientific evidence published to date to analyze the effectiveness of VRBT on the impact of FMS and in other related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Balneotherapy, a form of hydrotherapy that involves immersion in mineral-rich water, has been studied for its potential benefits in fibromyalgia patients [ 93 ]. Future research could further explore the effects of balneotherapy on fibromyalgia symptoms and identify the optimal treatment protocols.…”
Section: Reviewmentioning
confidence: 99%